Granulomatosis with Polyangiitis Presenting as Pauci-Immune Crescentic Glomerulonephritis in Pregnancy - Ryan Kunjal; Raafat Makary; Andreea Poenariu (Case Reports in Nephrology)
Antineutrophil cytoplasmic antibody (ANCA) associated vasculitis rarely affects females of reproductive age. A 28-year-old African American woman presented at 8 weeks of gestation with intractable vomiting attributed to hyperemesis gravidarum. She was found to have acute kidney injury that was unresponsive to vigorous fluid resuscitation and urine sediment examination was suggestive of an underlying glomerulonephritis. Serum c-ANCA and PR3 were elevated and there was no peripheral eosinophilia. During her course she also developed one episode of small volume hemoptysis with right upper lobe infiltrates on CT Chest. There were no cutaneous manifestations of vasculitis or upper respiratory symptoms. Renal biopsy revealed a pauci-immune crescentic glomerulonephritis (PICGN). The diagnosis was consistent with granulomatosis with polyangiitis (GPA). Management initially comprised teratogen sparing agents; steroids, intravenous immunoglobulin; and plasma exchange. The response was suboptimal and she became dependent on daily renal replacement therapy. Ultimately the pregnancy was terminated allowing for traditional treatment approaches with dramatic effect. This is the first case of GPA presenting as PICGN in pregnancy and highlights the challenges of its management.